APPLICATION OF ISLAMIC COUNSELING GUIDANCE IN OVERCOMING JUVENILE DELINQUENCY IN MAS ISLAMIYAH SUNGGAL - Lubis, Saiful Akhyar; Abdurahman, Abdurahman; Rahmayani, Siti (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
This study aims to determine (1) the type of behavior of juvenile delinquency among students Mas Islamiyah Medan Sunggal and its causes, (2) the application of Islamic counseling to juvenile delinquency among students Mas Islamiyah Medan Sunggal, and (3) behavioral changes in juvenile delinquency among students Mas Islamiyah Medan Sunggal after receiving Islamic counseling services. This research is qualitative research using the field research. The data collection technique is done by (1) observation/observation, (2) Interviews, and (3) document study. Data analysis techniques are data reduction, display, and conclusion drawing/verification. The results obtained are (1) Mas Islamiyah Sunggal can be identified problems that occur as follows, namely dating, stealing, and Fighting, and (2) juvenile delinquency that students in MAS Islamiyah Sunggal have is not left alone, but in finding a way out so that the students out of the problem in the form of Islamic counseling guidance with appropriate methods, (3) after receiving, the result is that students who make behavioral deviations can accept and change for the better. Thus, Islamic counseling techniques can be used as an offer to solve all the problems of students in school. In a broader scope, the counselor can use Islamic counseling guidance to solve the twists and turns of life problems faced.